Framework for sensitization assessment of extractables and leachables in pharmaceuticals. (7th February 2022) - Parris, Patricia; Whelan, Geraldine; Burild, Anders; Whritenour, Jessica; Bruen, Uma; Bercu, Joel; Callis, Courtney; Graham, Jessica; Johann, Esther; Griffin, Troy; Kohan, Martin; Martin, Elizabeth A.; et al.
Abstract: During the toxicological assessment of extractables and leachables in drug products, localized hazards such as irritation or sensitization may be identified. Typically, because of the low concentration at which leachables occur in pharmaceuticals, irritation is of minimal concern; therefore, this manuscript focuses on sensitization potential. The primary objective of performing a leachable sensitization assessment is protection against Type IV induction of sensitization, rather than prevention of an elicitation response, as it is not possible to account for the immunological state of every individual. Sensitizers have a wide range of potencies and those which induce sensitization upon exposure at a low concentration (i.e. strong, or extreme sensitizers) pose the highest risk to patients and should be the focus of the risk assessment. The Extractables and Leachables Safety Information Exchange (ELSIE) consortium has reviewed the status of dermal, respiratory, and systemic risk assessment in cosmetic and pharmaceutical industries, and proposes a framework to evaluate the safety of known or potential dermal sensitizers in pharmaceuticals. Due to the lack of specific regulatory guidance on this topic, the science-driven risk-based approach proposed by ELSIE encourages consistency in the toxicological assessment of extractables and leachables to maintain high product quality and ensure patient safety.